The Impact of COVID-19 Pandemic on Stress and Anxiety of Non-infected Pregnant Mothers - A Mehdizadehkashi; Sh Chaichian; L Haghighi; N Eshraghi; A Bordbar; N Hashemi; R Derakhshan; Sh Mirgalobayat; S Rokhgireh; K Tahermanesh (JRI, 2021)
Background: The newly emerging COVID-19 has caused severe anxiety around the world and it is infecting more people each day since there is no preventive measure or definite therapy for the diseases. The present study aimed to evaluate its effect on anxiety and stress of pregnant mothers during perinatal care. Methods: Three–hundred pregnant mothers without COVID–19 infection who were referred to the hospitals affiliated to Iran University of Medical Sciences for delivery during April 2020, based on negative clinical symptoms and the results of polymerase chain reaction (rt-PCR) for COVID–19, were recruited by census method and asked to complete the Persian version of the perceived stress scale (PSS); participants views about their anxiety level and the role of COVID–19 as the source of their stress and worries were recorded. Women who refused to continue the study were excluded. The frequency of variables and mean scores were calculated using SPSS v. 21. Results: Mean age of mothers was 30.20±16.19 years; 31.3% were primigravida and mean gestational age was 38.00±4.14 weeks. Moreover, 16.3% asked for earlier pregnancy termination and 39% requested Cesarean section (C/S). Assessing the mothers’ anxiety revealed a high/very high level of anxiety in 51.3%. The majority felt worried and frustrated because of COVID–19 (86.4%). Social media had a great impact on the level of stress among these mothers (60.3%). Conclusion: COVID-19 pandemic is an important source for the increased anxiety and stress among healthy pregnant mothers.